AI-based targeted advertising system - Tew Jia Yu; Chin Poo Lee; Kian Ming Lim; Siti Fatimah Abdul Razak (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
The most common technology used in targeted advertising is facial recognition and vehicle recognition. Even though there are existing systems serving for the targeting purposes, most propose limited functionalities and the system performance is normally unknown. This paper presents an intelligent targeted advertising system with multiple functionalities, namely facial recognition for gender and age, vehicle recognition, and multiple object detection. The main purpose is to improve the effectiveness of outdoor advertising through biometrics approaches and machine learning technology. Machine learning algorithms are implemented for higher recognition accuracy and hence achieved better targeted advertising effect.